2002
DOI: 10.1046/j.1460-9592.2002.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

1‐Year Performance of a Defibrillation Lead with a Small Electrode Surface for High Impedance Pacing: A Randomized, Controlled Study

Abstract: A small electrode surface reduces pacing current drain and can extend generator longevity. The study evaluated the performance of a tined, quadripolar defibrillation lead (model 6944) that has a small-surfaced, steroid-eluting electrode tip for high impedance pacing. In a prospective, controlled study, 34 patients with conventional ICD indications were randomized one to one to receive the high impedance model 6944 or a tined defibrillation lead with a conventional sized, steroid-eluting electrode tip model 694… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Initial experience by Joglar et al 5 also suggested the possibility of a higher threshold when high impedance electrode was used. This study and several other studies have demonstrated stable electrical performance of high impedance electrodes during follow‐up 7–10,15,16 . The current drain was reduced by the high impedance leads and the battery longevity was extended 11,12 …”
Section: Discussionsupporting
confidence: 63%
“…Initial experience by Joglar et al 5 also suggested the possibility of a higher threshold when high impedance electrode was used. This study and several other studies have demonstrated stable electrical performance of high impedance electrodes during follow‐up 7–10,15,16 . The current drain was reduced by the high impedance leads and the battery longevity was extended 11,12 …”
Section: Discussionsupporting
confidence: 63%
“…In a recent study by Dorwarth et al, lead survival decreased from 98% at 4‐year follow‐up to only 62% at 8‐year follow‐up 5 . Newer defibrillation leads have a better overall clinical performance in the short term 6–8 . In any case, lead system failure places patients with ICDs at risk for delivery of inappropriate shocks and may even result in sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%
“…5 Newer defibrillation leads have a better overall clinical performance in the short term. [6][7][8] In any case, lead system failure places patients with ICDs at risk for delivery of inappropriate shocks and may even result in sudden cardiac death. Measurements of pacing and high-voltage impedance are routinely performed during outpatient ICD visits, but intermittent discontinuity in lead conductor integrity can be difficult to detect or confirm.…”
Section: Discussionmentioning
confidence: 99%